2014
DOI: 10.1155/2014/804654
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Serum Biomarkers and Clinical Factors on Intensive Care Unit Mortality and 6-Month Outcome in Relatively Healthy Patients with Severe Pneumonia and Acute Respiratory Distress Syndrome

Abstract: Objectives. This study aimed to identify the independent biomarkers and clinical factors that could predict ICU mortality and 6-month outcomes in relatively healthy patients with severe pneumonia and acute respiratory distress syndrome (ARDS). Patients and Methods. We prospectively enrolled patients with severe pneumonia-related ARDS that required mechanical ventilation. Patients were excluded if they were unable to take care of themselves. Several biomarkers and clinical factors were evaluated prospectively o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…HMGB1 is a highly conserved non-histone chromosome binding protein, which is closely related to a variety of lung diseases, including pneumonia (Tseng et al, 2014), tuberculosis (Zeng et al, 2015), chronic obstructive pulmonary disease (Sukkar et al, 2012), pulmonary fibrosis (Smit et al, 2014), and lung transplantation (Weber et al, 2014). Normally, HMGB1 is mainly concentrated in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is a highly conserved non-histone chromosome binding protein, which is closely related to a variety of lung diseases, including pneumonia (Tseng et al, 2014), tuberculosis (Zeng et al, 2015), chronic obstructive pulmonary disease (Sukkar et al, 2012), pulmonary fibrosis (Smit et al, 2014), and lung transplantation (Weber et al, 2014). Normally, HMGB1 is mainly concentrated in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive extracellular HMGB1 quantities cause tissue damage and organ dysfunction. In a clinical study, lethality in bacterial pneumonia complicated by ARDS was strongly predicted by initial appropriate antibiotic use and plasma HMGB1 levels (Tseng et al 2014). Treatment with HMGB1-specific antagonists ameliorates inflammation and improves survival in many preclinical models of acute or chronic inflammatory diseases (Andersson and Tracey 2011;Kang et al 2014;Andersson et al 2018b;Yang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not statistically significant in multivariate analysis. This may be due to the small sample size (n=56) 42. In contrast, on meta-analysis carried out by Terpstra et al,23 IL-8 was independently associated with the outcome of ARDS with OR 3.35 (1.96-5.71) 7.…”
Section: Interluken-8mentioning
confidence: 86%
“…The high serum level of IL-8 is associated with severe illness and mortality 41. Tseng et al42 found that higher levels of IL-8 was observed in ICU non-survivors. However, it is not statistically significant in multivariate analysis.…”
Section: Interluken-8mentioning
confidence: 99%